E-POSYANDU : SISTEM PENGARSIPAN POSYANDU GUNA EFISIENSI PENDATAAN KESEHATAN PASIEN POSYANDU - Ahmad Wali Satria Bahari Johan; Rizky Fenaldo Maulana; Kharisma Monika Dian Pertiwi (Politeknik Negeri Sriwijaya, 2022)
Posyandu Dinoyo is one of the posyandu located in Malang City, East Java. Until now, Posyandu Dinoyo is still active in carrying out posyandu activities. However, in carrying out these activities, Dinoyo Posyandu cadres find it difficult. Posyandu cadres collect public health data on health cards. Posyandu cadres are required to keep these cards. Posyandu cadres have difficulty finding a resident's health document. Posyandu cadres are also worried if the card is lost or damaged. Posyandu cadres must also provide data collection results to puskesmas officers every month. Therefore, the IT Telkom Surabaya community service team created a system that was able to facilitate posyandu cadres in carrying out their duties. Our team has created a system that can record people's health and their health. In addition, data can be exported in PDF and excel formats for monthly reporting. After the system is complete, Posyandu cadres can easily save each inspection data into the system without the need to prepare a form to store inspection data. Posyandu cadres can easily control health data and easily access or search for desired patient data. Where previously they had to search in the pile of documents that were quite a lot. Reports of inspection results can be easily made because the system has provided tools to print reports that are ready to be submitted to the Puskesmas.